Room Borrowing Information System Website Based using PHP and MySQL with Waterfall Model - Doni Oktaviana; Mustofa Abi Hamid (Journal of Vocational Education Studies, 2021)
Research by developing an information system is a research that aims to produce and develop an information service system design in the form of website-based rooms lending using PHP as a programming language and MySQL as a database that will be used at the Faculty of Teacher Training and Education, Sultan Ageng Tirtayasa University in-room management as room loan, room loan schedule, room loan data, and room information. This study uses the waterfall development model, with 5 (five) stages of development including the stages of communication, planning, modelling, construction and deployment. This research used Alpha and Beta testing to 3 (three) media experts and 31 (thirty-one) users including 1 (one) admin and 30 (thirty) students. Data collection techniques using interview techniques, observation and dissemination of research instruments. With data analysis in the form of a feasibility test using a Likert scale instrument of 4 (four) assessment scores to media experts and respondents. The final product produced is a website for rooms loaning information system, by average score by media experts (Alpha Testing) of 71.6 with the "very feasible" category. The results of the feasibility test by users (Beta Testing) were 34.32 with the "very feasible" category. Therefore, it can be concluded that the website-based room loan information system is very feasible to use.